2022
DOI: 10.25046/aj070103
|View full text |Cite
|
Sign up to set email alerts
|

Value Trace Problems for Code Reading Study in C Programming

Abstract: and understand their behaviors to be familiar to the programming paradigm. Unfortunately, effective tools to support independent code reading study at home have not been well designed. Heretofore, we have proposed the value trace problem (VTP) for Java programming. A VTP instance consists of one source code, several questions, and the correct answers to them. Each question asks the value of a critical variable or output message in the source code. The correctness of any student answer is checked instantly by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To enhance C programming studies, we have developed a web-based C programming learning assistance system (CPLAS). CPLAS offers a variety of programming exercise problems at different levels, including the grammar-concept understanding problem (GUP) [3], the value trace problem (VTP) [4], the element fill-in-blank problem (EFP) [5], the code completion problem (CCP) [6], and the phrase fill-inblank problem (PFP) [7]. In any problem type, the answer from a student is instantly marked through string matching with the stored correct one at the offered answer interface using a web browser [8].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance C programming studies, we have developed a web-based C programming learning assistance system (CPLAS). CPLAS offers a variety of programming exercise problems at different levels, including the grammar-concept understanding problem (GUP) [3], the value trace problem (VTP) [4], the element fill-in-blank problem (EFP) [5], the code completion problem (CCP) [6], and the phrase fill-inblank problem (PFP) [7]. In any problem type, the answer from a student is instantly marked through string matching with the stored correct one at the offered answer interface using a web browser [8].…”
Section: Introductionmentioning
confidence: 99%
“…PLAS provides several types of programming problems that have diverse solving difficulties and learning goals, so that a student can gradually advance the learning stage of PLAS. They include the grammar-concept understanding problem (GUP) [2], the value trace problem (VTP) [3]- [5], the code modification problem (CMP) [6], the element fill-in-blank problem (EFP) [7], [8], the code completion problem (CCP) [9], and the code writing problem (CWP) [10]. For any problem type, the correctness of an answer from a student is checked automatically by unit testing in CWP or string matching with the stored correct answer in the others.…”
Section: Introductionmentioning
confidence: 99%
“…To assist self-studies of C programming, we have studied C programming learning assistant system (CPLAS) [1] by extending the previous works for Java programming learning assistant system (JPLAS) [2]. To learn programming effectively, we have suggested that students should solve simple grammar concepts problems while reading simple source codes first.…”
Section: Introductionmentioning
confidence: 99%